PENGUATAN UMKM BERBASIS KEARIFAN LOKAL DALAM MENDUKUNG PENGEMBANGAN EKOWISATA DI DESA RENAH ALAI, KEC. JANGKAT - Riri Wulandari; Gion Rahmadan; Kusaimah; Hayati (Hira Institute, 2025)
This community service program aims to strengthen local wisdom-based Micro, Small, and Medium Enterprises (MSMEs) in Jangkat Region to support sustainable ecotourism development. Jangkat has significant ecotourism potential supported by natural beauty, biodiversity, and rich cultural values; however, local MSMEs have not been optimally integrated into the tourism sector due to limited product innovation, packaging quality, branding, and marketing capacity. The program employed a participatory and sustainable approach through coordination, needs assessment, training, mentoring, and monitoring-evaluation. Activities focused on improving human resource capacity, developing and innovating local products, enhancing packaging and branding, and strengthening both conventional and digital marketing strategies aligned with ecotourism activities. The results indicate increased knowledge and skills of MSME actors, improved product quality and identity based on local wisdom, and stronger integration of MSMEs into the ecotourism value chain. These improvements contributed to greater product competitiveness, expanded market access, and increased community income. Strengthening local wisdom-based MSMEs is therefore an effective strategy to promote sustainable ecotourism, enhance the creative economy, and preserve cultural and environmental values in Jangkat Region.